European Centre for Development Policy Management | Home (ECDPM)
ECDPM is a think and do tank. Our main goal is to broker effective development partnerships between the EU and the Global South, particularly Africa.
UA-9c040d93-d6c4-41e4-93a1-c916ce397bfe KerkoCite.ItemAlsoKnownAs: 2129771:ANGVJEHL 2317526:CB97VIIM
Keywords: -FullBiblioUHMLgen; -GeneralCitations; Networks; publicImportV1